(untitled) (Bangladesh Journal of Animal Science, 2014)
The study was conducted to ascertain the injuries of cattle and buffaloes at selected livestock markets of Bangladesh during transportation and slaughter. A total of 290 (212 cattle and 78 water buffalo) at Sagorica cattle market and 57 (24 cattle and 33 buffalo) at Fringibazar and Pahartali slaughter houses of Chittagong were examined during the period from January to April 2013. The frequency of different injuries during handling, transportation and slaughtering were assessed. The data of different type of injuries (e.g. abrasion, laceration, bleeding, swelling, scarification and wound) were collected from the market and slaughter houses by using visual observation and palpation method. The frequency of abrasion, laceration, bleeding, swelling and scarification of cattle were 73, 45, 4, 3, 67 and 87%, and of buffaloes were 71, 9, 23 nd 41%, respectively. All the injuries were higher in Haryana than Rajasthani, Shahiwal and Exotic non descriptive cattle breeds. The tail injury in cattle and buffaloes was 65 and 23%, respectively. In the slaughter house, the frequency of abrasion, laceration, penetration and scarification were 79, 75, 8, 75 in cattle, and 85, 70, 0 and 67% in buffaloes, respectively. From these findings it could be concluded that proper handling and care should be taken to avoid different injuries of cattle and buffaloes during transportation and slaughter. DOI: http://dx.doi.org/10.3329/bjas.v43i1.19389 Bang. J. Anim. Sci. 2014. 43 (1): 74-77